2017
DOI: 10.1016/j.jpeds.2016.12.058
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Socioeconomic Status, Family Income, and Measures of Muscular and Cardiorespiratory Fitness in Colombian Schoolchildren

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 28 publications
6
28
1
1
Order By: Relevance
“…These studies drew predominantly from cross-sectional data and did not account for a range of potential confounders, including contextual factors that contribute to absenteeism and fitness. For example, neighborhood poverty contributes to parent–school engagement and youth fitness (18,19). Similarly, school size affects programs and policy toward school attendance and physical activity (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…These studies drew predominantly from cross-sectional data and did not account for a range of potential confounders, including contextual factors that contribute to absenteeism and fitness. For example, neighborhood poverty contributes to parent–school engagement and youth fitness (18,19). Similarly, school size affects programs and policy toward school attendance and physical activity (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…This may have limited our findings given that both individual-level and area-level socioeconomic factors can be independent predictors of health behaviour. However, recent work has shown that when area-level poverty is considered, no differences in the association of socioeconomic status and youth cardiovascular fitness are found due to family income 34. Also, given home-area poverty is often included as a potential confounder in analyses to account for poverty’s influence on health, we conducted sensitivity analyses replacing park-area poverty with a variable representing the child’s home-area poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Children from less‐deprived areas (or from families of higher SES) have better aerobic and muscular fitness than those in low‐SES groups (Jiménez‐Pavón et al, ; Jin & Jones‐Smith, ). Children in higher SES groups are also taller and have greater lean body mass than those of lower SES (Monyeki et al, ; Sandercock, Lobelo, & Correa‐Bautista, ).…”
Section: Introductionmentioning
confidence: 99%
“…The superior fitness of children from high‐SES backgrounds has been attributed to differences in habitual physical activity between SES groups (Esmaeilzadeh, Kalantari, & Nakhostin‐Roohi, ; Jiménez‐Pavón et al, ; Vandendriessche et al, ). Differences in muscular fitness could also be the product of SES‐related differences in body dimensions (Monyeki et al, ; Sandercock et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation